2021
DOI: 10.3389/fbioe.2020.613784
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Therapeutic Effects and Mechanisms of Hydroxyasiaticoside Combined With Praziquantel in the Treatment of Schistosomiasis Induced Hepatic Fibrosis

Abstract: Schistosomiasis has been a fatal obstinate disease that threatens global human health, resulting in the granulomatous inflammation and liver fibrosis.Objective:The aim of this study was to evaluate the therapeutic effects and mechanisms of hydroxyasiaticoside combined with praziquantel in the treatment of schistosomiasis-induced liver fibrosis.Methods:Mice were randomly distributed into four experimental groups: normal control group, model group, praziquantel group, praziquantel + hydroxyasiaticoside group. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…In this study, we document an evident antifibrotic effect of resveratrol in schistosomal hepatic fibrosis and delineate some contributing mechanisms. In accordance with previous studies (Fang et al 2021 ) (El-Lakkany et al 2012 ), the untreated S. mansoni infected mice showed an elevation in serum levels of liver enzymes reflecting the loss of hepatocyte integrity, whereas the detected hypoalbuminemia could be the result of decreased albumin synthesis from damaged hepatocytes or due to decreased absorption from damaged intestinal mucosa (Al Humayed et al 2020 ; El-Lakkany et al 2012 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we document an evident antifibrotic effect of resveratrol in schistosomal hepatic fibrosis and delineate some contributing mechanisms. In accordance with previous studies (Fang et al 2021 ) (El-Lakkany et al 2012 ), the untreated S. mansoni infected mice showed an elevation in serum levels of liver enzymes reflecting the loss of hepatocyte integrity, whereas the detected hypoalbuminemia could be the result of decreased albumin synthesis from damaged hepatocytes or due to decreased absorption from damaged intestinal mucosa (Al Humayed et al 2020 ; El-Lakkany et al 2012 ).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, prevention of fibrosis remains the only feasible strategy available (Kong et al 2020 ). Though very few agents (e.g., pirfenidone and nintedanib) have recently been approved for pulmonary fibrosis, an effective antifibrotic drug that can be used safely in liver fibrosis is considered a big challenge (Fang et al 2021 ). Therefore, promising plant-derived compounds possessing pleiotropic pharmacological actions with a long history of safety, such as resveratrol, merits attention (Koushki et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings strongly suggest that although LFD is not associated with hyperlipidemia, the upregulation of CD36 by GPR40 KO increases lipid uptake and hepatic inflammation, contributing to hepatic steatosis, inflammation and fibrosis. Consistently, we showed that GPR40 KO in LFD-fed LDLR-deficient mice increased hepatic expression of aSMA, TGFβ1, IL-6 and TNFα, which are key molecules involved in hepatic fibrosis and inflammation [67,68].…”
Section: Plos Onesupporting
confidence: 70%
“…After sectioning, these tissues were assessed with hematoxylin and eosin (H&E) staining to observe the pathological changes under a microscope. In addition, the kidney and liver tissues were investigated by Masson staining to evaluate the histology of organ fibrosis, and the pathological scores of kidney and liver tissues were calculated per the method of Fang et al ( 31 ).…”
Section: Methodsmentioning
confidence: 99%